MUSEUMS AS A MEDIUM AND SOURCE OF LEARNING - Wahidin, Unang; Prihandini, Dika; Wulandari, Novi Ayu; Wardah, Siti Zulfa Tri; Anggraeni, Wulan (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Learning is an activity that involves teachers and students in interacting. However, in reality, not a few students are not directly involved in learning, meaning that students play a passive role during the learning process. This can be caused in part by teachers' ignorance in the effectiveness of the use of learning media, so that students' motivation to learn decreases. Purpose: This literature study aims to find out how museums are used as a medium and source of learning, as well as analyze the obstacles and solutions of the factors that hinder their use. Method: The type of research used is a literature review using a descriptive method. Result: The results of the study show that museums can be used as a medium and learning resource because they can help teachers carry out learning outside the classroom, help increase student knowledge and understanding, and increase student motivation and participation during the learning process. As for the obstacles in its use, namely limited time and funds, as well as museum collections that are not relevant to what students are studying, the solution in handling it is to prepare a mature schedule and submit a budget to the school for student personal cost relief, then be able to adjust the museum and more relevant materials.